The Impact of Machine Learning on the Future of Insurance Industry - Paruchuri, Harish (American Journal of Trade and Policy, 2020)
Recently data remains the central and the core concentration in the insurance industry. The outburst in data generation thus created the need for technologies that will be used to process or manage big data in the industry. Thus, the conditions at hand are sighted by a plodding but firm change, which is compelled by an atmosphere shown by enhanced rivalry, fraud activities, flexible market places, high prospects from clients, and stringent guidelines. The introduction of machine learning in solving industry tasks in the assurance value chain such as underwriting and forfeiture avoidance, entitlements management, fraud uncovering, product evaluating, transactions, and client capability will put the industry in the damp light in the future due to high increase of big data. This paper has examines some cases and bring out the vital role of machine learning in handling client data and resolving issues of entitlements. Hence, machine learning holds a brighter future for insurance organizations if implemented well.